Desain Interior Coffee Shop di Denpasar dan Loyalitas Konsumennya : Generasi Y dan Z: Generasi Y dan Z - Susanti, Ardina; Triana Dewi, Putu Surya; Adnyana Putra, I Wayan Yogik (Program Studi Desain Interior Unikom, 2021)
Many local coffee shop brands are also present to enliven the coffee shop market in Bali, especially in Denpasar City. This actually presents a new phenomenon that affects the interior design of a coffee shop, that no longer emphasizes the area of ​​the coffee shop space, but presents a simpler interior design character with a unique theme. This variation also has its own consumer segmentation. Therefore, this study aims to assess the correlation of the sensuality value of the coffee shop brand with the level of consumer loyalty to the coffee shop brand. This is important to research further, because it can see in detail about the role of interior design on a coffee shop brand and also on people's consumption patterns. This study uses a mixed-method sequential method using questionnaire data collection methods for generations Y and Z, observation and direct interviews with consumers and coffee shop owners. The results of this study indicate that the coffee shop interior elements that have impact to the level of consumer loyalty are physical environmental factors such as furniture, lighting, color combinations, interior decoration, sound, temperature, good coffee quality, which will affect the pleasant aroma of coffee shop, as well as non-physical environmental factors such as social interactions that can increase comfort, feels like home, at a coffee shop.